RNA Editing in Mitochondria and Plastids: Weird and Widespread - Lukeš, Julius; Kaur, Binnypreet; Speijer, Dave (Trends in genetics, 2021)
Though widespread, RNA editing is rare, except in endosymbiotic organelles. A combination of higher mutation rates, relaxation of energetic constraints, and high genetic drift is found within plastids and mitochondria and is conducive for evolution and expansion of editing processes, possibly starting as repair mechanisms. To illustrate this, we present an exhaustive phylogenetic overview of editing types.
Keywords: Mitochondria; Symbiosis; Mutation Rate; mutace; Plastids; editace RNA; plastidy; Mutation; RNA Editing; mitochondrie; symbióza; Phylogeny; fylogeneze; mutační rychlost